2008
DOI: 10.1103/physrevd.78.083504
|View full text |Cite
|
Sign up to set email alerts
|

Chemical potential and the nature of dark energy: The case of a phantom field

Abstract: The influence of a possible non zero chemical potential µ on the nature of dark energy is investigated by assuming that the dark energy is a relativistic perfect simple fluid obeying the equation of state (EoS), p = ωρ (ω < 0, constant). The entropy condition, S ≥ 0, implies that the possible values of ω are heavily dependent on the magnitude, as well as on the sign of the chemical potential. For µ > 0, the ω-parameter must be greater than -1 (vacuum is forbidden) while for µ < 0 not only the vacuum but even a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 76 publications
2
36
0
Order By: Relevance
“…and as can be observed for the phantom regime we have T S < 0 since ω < −1, this implies a negative entropy for the phantom cosmology. Within the scheme of standard cosmology was found that the aforementioned problem for the entropy can be solved if a chemical potential, denoted as μ, it is introduced at cosmological level [61,62], i.e., the Euler relation takes the form…”
Section: Thermodynamicsmentioning
confidence: 99%
“…and as can be observed for the phantom regime we have T S < 0 since ω < −1, this implies a negative entropy for the phantom cosmology. Within the scheme of standard cosmology was found that the aforementioned problem for the entropy can be solved if a chemical potential, denoted as μ, it is introduced at cosmological level [61,62], i.e., the Euler relation takes the form…”
Section: Thermodynamicsmentioning
confidence: 99%
“…The evolutions of all effective EoS, whose early-time asymptotic values are ω 1e f f = 0. 44, ω 2e f f = −1. 47 and ω t = 0, are shown in Fig.…”
Section: α =mentioning
confidence: 99%
“…Thus, this idea of negative temperature is discarded because the temperature of a fluid should be positive-definite. Another possible way is the establishment of a negative potential to the fluid [42] to validate the hypothesis of the phantom. However, the generalized second law of thermodynamics postulates that the total entropy S of the universe should increase with time during cosmological evolution, i.e.…”
Section: Field Equations and Thermodynamicsmentioning
confidence: 99%